Nutritive value of rations containing sugar cane, poultry litter and corn - Pastori, Angela M.; de Andrade, Pedro; Sampaio, Alexandre A. Moraes; Rosa, Luis C. de Andrade; Andrade, Antonio Tadeu de; Oliveira, Mauro Dal Secco de (Pesquisa Agropecuaria Brasileira, 2014)
This work was conduced at Faculdade de Ciências Agrárias e Veterinárias, Campus de Jaboticabal-UNESP, São Paulo, Brazil, with the objective of finding out the intake and apparent digestibility of the nutrients in rations with different proportions of sugar cane (SC) and poultry litter (PL): 65.50 : 34.50%; 58.00 : 42.00% and 52.00 : 48.00% combined with three levels of corn: 0; 0.15 kg an 1,50 kg. Treatments were studied according to a completely randomized block design 32 with three replications. Nine steers with an initial average weight of 334 kg were used. Linear regression studies showed significant effects (P < 0.01) of the different levels of corn on apparent digestibility of the dry matter, organic matter, ether extract, nitrogen free extract and total digestible nutrients. Proportions of SC/PL with lower sugarcane ration increased crude fiber and protein digestibility (P < 0.01). There was no significant interaction of the levels of corn and different proportions of sugarcane to poultry litter. Nutritive value and total intake of dry matter increased with the levels of corn in the ration (P < 0.01).
Keywords: dry matter digestibility; intake